Evaluasi dan Penguatan Tata Kelola Sistem Informasi E-Prakerin dengan Framework COBIT 2019: Perspektif Integrasi Kecerdasan Buatan - Fajar Indra Nur Alam; Bawazir Fadhil Muhammad; Ani Dijah Rahajoe (Lembaga Yasin AlSys, 2026)
The E-Prakerin Information System at PT. XYZ serves as the digital backbone for the management of industrial work practice, and therefore requires mature information technology governance as well as readiness for artificial intelligence (AI) integration. This study aimed to evaluate the maturity level of E-Prakerin Information System governance based on the COBIT 2019 framework and to analyze the system’s readiness for AI integration. An evaluative approach was employed, with data collected through interviews, observations, and questionnaires, which were mapped onto the five COBIT 2019 domains: EDM, APO, BAI, DSS, and MEA. The maturity level was calculated using a 0–5 scale. The results show that the average maturity level is at 2.48 (Managed Process), indicating that processes are in place but have not yet been fully documented and measured. Gap analysis reveals the largest shortfalls in the strategic planning (APO) and monitoring (MEA) domains. In addition, K-Means clustering of questionnaire responses successfully grouped stakeholder perceptions into three main segments that serve as the basis for determining improvement priorities. Based on these findings, the study proposes a roadmap for enhancing governance toward level 4 (Quantitatively Managed) and a model for integrating AI features, such as automated document verification and quota prediction, to close existing gaps. This study contributes to the development of a holistic evaluation framework that integrates IT governance auditing with readiness analysis for emerging technologies.